Taxonomic revision of the Colombian Tityus (Archaeotityus) (Scorpiones, Buthidae) species: a morphological and morphometric approach, with a description of a new species - Moreno-González, Jairo A.; González O., Ranulfo; Flórez D., Eduardo (Zootaxa, 2019)
We present a taxonomic revision of the Colombian Tityus (Archaeotityus) species based on morphological and morphometric evidence. We examined more than 385 specimens and evaluated new and previously used qualitative and quantitative morphological characters. We redescribe the Colombian species and present morphological characters for both sexes and an emended diagnosis for the subgenus Tityus (Archaeotityus). We describe a new species Tityus guane sp. nov. from Santander department, Colombia, Tityus betschi Lourenço 1992 is synonymized with Tityus parvulus Kraepelin, 1914, and Tityus wayuu Rojas-Runjaic & Armas, 2007 is synonymized with Tityus tayrona Lourenço, 1991. We measured 186 specimens and performed a multivariate principal component analysis (PCA) for 34 selected morphometric ratios for each sex. We found that a few morphological ratios support species level distinctions within the Colombian species. We provide updated distributional maps with new records and an identification key for both sexes. Furthermore, we provide an updated checklist for the subgenus and a discussion about the character systems used within Tityus (Archaeotityus). The new morphological characters proposed and the traditional morphometry examined with a PCA are useful for studying Tityus (Archaeotityus) taxonomy.